Can on-site management mitigate nitrogen deposition impacts in non-wooded habitats?. (August 2017) - Jones, L.; Stevens, C.; Rowe, E.C.; Payne, R.; Caporn, S.J.M.; Evans, C.D.; Field, C.; Dale, S.
Abstract: Nitrogen (N) deposition is a major cause of plant biodiversity loss, with serious implications for appropriate management of protected sites. Reducing N emissions is the only long-term solution. However, on-site management has the potential to mitigate some of the adverse effects of N deposition. In this paper we review how management activities such as grazing, cutting, burning, hydrological management and soil disturbance measures can mitigate the negative impacts of N across a range of temperate habitats (acid, calcareous and neutral grasslands, sand dunes and other coastal habitats, heathlands, bogs and fens). The review focuses mainly on European habitats, which have a long history of N deposition, and it excludes forested systems. For each management type we distinguish between actions that improve habitat suitability for plant species of conservation importance, and actions that immobilize N or remove it from the system. For grasslands and heathlands we collate data on the quantity of N removal by each management type. Our findings show that while most activities improve habitat suitability, the majority do little to slow or to reduce the amount of N accumulating in soil pools at current deposition rates. Only heavy cutting/mowing with removal in grasslands, high intensity burns in heathlands and sod cutting remove more N than comes in from deposition under typical management cycles. We conclude by discussing some of the unintended consequences of managing specifically for N impacts, which can include damage to non-target species, alteration of soil processes, loss of the seedbank and loss of soil carbon. Highlights: We show how management mitigates nitrogen impacts in grasslands, heathlands, bogs. We distinguish between effects on habitat suitability and on nitrogen removal. All management options considered can improve habitat suitability. But, the majority of options remove little or no nitrogen from the system. Managers should consider habitat suitability, N removal, and unintended consequences.